2020
DOI: 10.3390/polym12071607
|View full text |Cite
|
Sign up to set email alerts
|

Marked Difference in the Conformational Transition of DNA Caused by Propanol Isomer

Abstract: We measured the changes in the higher-order structure of DNA molecules (λ phage DNA, 48 kbp) at different concentrations of 1- and 2-propanol through single-molecular observation. It is known that 2-propanol is usually adapted for the procedure to isolate genomic DNA from living cells/organs in contrast to 1-propanol. In the present study, it was found that with an increasing concentration of 1-propanol, DNA exhibits reentrant conformational transitions from an elongated coil to a folded globule, and then to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…A comparative study between single DNA observation and CD measurement indicated that the reentrant transition of the secondary structure corresponds to the reentrant transition of the higher-order structure (i.e., coil → compact → coil conformation) [ 3 ]. A similar reentrant transition of the higher-order structure of DNA was also observed with increasing concentrations of 1-propanol above 50% [ 7 ]. However, individual DNA molecules underwent a continuous transition, with gradual shrinking, from an elongated coil into a compact globule with 2-propanol.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…A comparative study between single DNA observation and CD measurement indicated that the reentrant transition of the secondary structure corresponds to the reentrant transition of the higher-order structure (i.e., coil → compact → coil conformation) [ 3 ]. A similar reentrant transition of the higher-order structure of DNA was also observed with increasing concentrations of 1-propanol above 50% [ 7 ]. However, individual DNA molecules underwent a continuous transition, with gradual shrinking, from an elongated coil into a compact globule with 2-propanol.…”
Section: Introductionsupporting
confidence: 57%
“…Although it is difficult to ascertain the underlying mechanism of the promotive effect at present, a weak increase in the viscoelasticity of DNA may correlate with transcription and translation efficiency. We recently reported the effect of 1-propanol and 2-propanol on the conformation of DNA based on the single DNA observation and CD measurement [ 7 ]. This study found that the hydrodynamic radius R H of T4 GT7 DNA tends to decrease when alcohol is added.…”
Section: Discussionmentioning
confidence: 99%